2005
DOI: 10.1002/jgm.772
|View full text |Cite
|
Sign up to set email alerts
|

Potocytosis and cellular exit of complexes as cellular pathways for gene delivery by polycations

Abstract: The different pathways of complex trafficking observed in relation with complex size imply the development and study of vectors forming complexes with definite size. Moreover, the complex exit we describe may contribute to the well-established short-term efficiency of gene transfer based on synthetic vectors. It favors the engineering of vectors allowing repeated treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 36 publications
(55 reference statements)
3
66
2
Order By: Relevance
“…The results of the present study are consistent with prior studies showing that large latex beads preferentially enter via caveolar endocytosis, although the mechanism is unclear [24,25]. However, other studies showed that particles with sizes exceeding 200 nm were internalized via macropinocytosis rather than caveolar endocytosis [26]. Taken together, these results suggest that the preferred cellular uptake pathway of IRQ-Lip particles could not be simply discussed by its physicochemical properties such as charge and size.…”
Section: Resultssupporting
confidence: 91%
“…The results of the present study are consistent with prior studies showing that large latex beads preferentially enter via caveolar endocytosis, although the mechanism is unclear [24,25]. However, other studies showed that particles with sizes exceeding 200 nm were internalized via macropinocytosis rather than caveolar endocytosis [26]. Taken together, these results suggest that the preferred cellular uptake pathway of IRQ-Lip particles could not be simply discussed by its physicochemical properties such as charge and size.…”
Section: Resultssupporting
confidence: 91%
“…Lanes 3-14: polyplexes of pEGFP (0.2 μg) with G6 (lanes 3, 4, 5), G6-4% PEG (lanes 6, 7, 8), G6-8% PEG (lanes 9, 10, 11), or G6-15% PEG (lanes 12, 13, 14). Each kind of dendrimer was used to form polyplexes with pEGFP in serum-free DMEM at three different N/P ratios of 1, 5, and 10, respectively dominant internalization pathway for polyplexes reported in the literature (39)(40)(41).…”
Section: Size and ζ Potential Of Peg-pamam Dendrimer/dna Polyplexesmentioning
confidence: 99%
“…In CLSM analyses of HUVEC and VSMC, pDNA transferred with cRGD-PEG-PAsp(DET) micelles tended to colocalize with lipid rafts and caveosomes, whereas pDNA after transfer with PEG-PAsp(DET) micelles tended to associate with acidic endosomes and lysosomes. Grosse et al 38 evaluated the cellular uptake of particles that were not installed with any ligands and showed that the process of cellular uptake depended upon particle size; particles with 4200 nm diameter were internalized by macropinocytosis, particles with 100-200 nm diameter by clathrin-mediated endocytosis and particles o100 nm diameter by caveolae-mediated endocytosis. The average diameter of cRGD-PEG-PAsp(DET) and PEG-PAsp(DET) micelles was around 100 nm, with a moderate distribution.…”
Section: Discussionmentioning
confidence: 99%